Sanitation, Hygiene, and Occupational Safety and Health in Community-Based Organic Waste Management: A Case Study of Legok Beterled, Bandung City - Lestari, Risma Neta; Astrid Nabillah; Neta Nabila Tricintiya; Firna Aulia Salsabila; Yani Achdiani (Jurnal Higiene Sanitasi, 2025)
Waste management remains a critical environmental and public health concern, particularly in urban settings such as Bandung, which previously faced a waste emergency due to landfill overcapacity. Legok Beterled has emerged as a community-based organic waste management model utilizing Black Soldier Fly (BSF) larvae. This study aims to describe the implementation of sanitation, hygiene practices, and occupational safety and health (OSH) at Legok Beterled, while identifying existing challenges and formulating recommendations for improvement. A qualitative descriptive method was employed through observations, in-depth interviews, and documentation involving one key informant selected using purposive sampling. Data were analyzed through data reduction, data display, and conclusion drawing. The findings show that sanitation conditions were relatively adequate, supported by the separation of processing units, utilization of natural ventilation, and application of Local Microorganisms (MOL) to minimize odors. Hygiene practices were reflected through regular handwashing and the separation of eating areas from workspaces; however, the use of personal protective equipment (PPE) remained inconsistent. OSH implementation was indicated by the availability of a first aid kit, evacuation routes, and proper sorting of sharp waste, although key facilities such as fire extinguishers and ergonomic workstations were still lacking. Major challenges included low community participation in source waste sorting, limited PPE supplies, insufficient financial support, and a shortage of human resources. This study highlights that systematic sanitation, hygiene, and OSH practices play a significant role in ensuring the sustainability of community-based organic waste management initiatives.